Буття літературного твору: аналіз та інтерпретація - Астрахан, Наталія; Astrakhan, Natalya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті аналіз художнього тексту та інтерпретація літературного твору розглядаються як необхідні чинники буття твору - події субстанціально значущої естетичної комунікації, що здійснюється на основі художнього тексту як матеріального об'єкта в процесі авторського творення та читацького відтворення. In the article the analysis of a fiction text and interpretation of literary works are seen as essential components of being a literary work - the events of the substantial significant aesthetic communication that take place on the basis of a fiction text as a material object in the process of copyright creation of authorship and readership. Genesis of a literary work is characterized as an integral part of universal existence, which is in accordance with the principle of the hermeneutic circle may indicate generally that remain unknown. The subordination of literary analysis fiction text and interpretation of literary works ontologically significant problems of human cognition and the world allows us to understand the Genesis of a literary work as an aesthetic sphere axiological unity of mankind, the awareness of the integrity of its cultural and historical development.
Genesis of a Literary Work: Analysis and Interpretation
Keywords: аналіз художнього тексту; інтерпретація літературного твору; analysis of a fiction text; the interpretation of a literary work